Degradação fotoquímica de efluentes industriais contendo polipropileno e isoniazida - Telemaco, Emmanuelle de Paiva (2008)
One of the main impacts to the environment is the water pollution, where the industrial sector is one of the main sources of this problem. In order to search for a solution, the industrial sector is looking forward to new technologies to treat its wastewaters with the goal to reuse the water in the own process. In this mode, the treatment presents a reduction in its costs with the water suply. One of these technologies that are getting more and more applications is the advanced oxidative processes (AOP´s). In this work two industrial wastewaters have been studied, i.e., containing polymers and pharmacus. In the case of the wastewaters with polymers the UV/H2O2 process has been applied with a systematic series of experiments, using irradiation from a mercury lamp and also solar. The following variables of the UV/H2O2 process for the polymers wastewaters have been studied systematically with the lamp reactor: mode of addition of hydrogen peroxide, temperature, time of reaction, hydrogen peroxide concentration and power of the lamp (80, 125, 250 and 400W). The results demonstrated to be satisfactory, obtaining rates of organic charge removal of 100% in 120 minutes of reaction. The studied variables for the experiments with solar irradiation using polymers wastewaters were only the time of reaction, the mode of addition and concentration of the hydrogen peroxide. The results with the solar irradiation demonstrated to be not satisfactory, reaching maximum of 22% of TOC removal in 240 minutes of reaction. This is in accordance with the fact that the solar source has only 5% of low UV irradiation. With respect to the photodegradation of the pharmacus wastewaters, the process UV/H2O2 and photo-Fenton have been applied. As a source of photons, in this case, a mercury UV lamp of 80 W has been used. The studied variables for the experiments with artificial irradiation with the pharmacus wastewaters were: initial concentration of the pollutant, concentration of Fe2+ and time of reaction. The results demonstrated a degree of degradation fairly satisfactory, showing a maximum conversion value of 46% in 120 minutes